A discourse about normalization or fantasy and Its reflections on everyday life: a cultural-historical analysis of two popular magazines of the 1950's, Bütün Dünya and Hafta - Özkan, Fulya. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2004., 2004)
Even though Turkey did not enter World War II officially, it was inevitable for her to be affected by a war that had repercussions throughout the world. Therefore, in a parallel fashion to the new developments following the war, the end of it marked a new era in Turkey as well. The economic prosperity that emerged relative to the harsh war conditions found its ideological reflections in the cultural realm, where a -so to speak- boom was observed. One consequence of this cultural proliferation was an increase in the number of popular culture magazines published in Turkey. Thus, this study presumes that an analysis of two major popular periodicals, Bütün Dünya and Hafta, is a good means to get an understanding of this transition period that followed the war. Accordingly, these two journals had a discourse parallel to the changing socio-economic environment of the post-war years in that they included articles about the entrepreneurial spirit in their pages. However, they reserved a place for a counter-discourse that challenged the industriousness and work ethics of this spirit as well. Moreover, the everyday life of the common people that was narrated in Hafta also constitutes a picture of the reality that contradicted such a discourse. This contradictory nature of the discourse of these two magazines also shapes the theoretical framework of this study in which recent discussions in the academic circles of both history and cultural studies disciplines are examined.
Keywords: World war, 1939-1945 -- Social conditions.